REBUILDING CORPORATE REPUTATION THROUGH FINANCIAL SIGNALING: THE MEDIATING ROLE OF PERFORMANCE IN CSR, TAX, AND COMPETITIVE STRATEGY - sari, petty aprilia; Hidayat, Imam; Goenawan, Yohanes August (COMPETITIVE, 2025)
The aim of this research is to investigate environmental issues that have a direct bearing on a Corporate reputation. The company's interest in and participation in social investments, such as Corporate Social Responsibility Disclosure, is one of them. 69 Manufacturing Companies with a listing period of 2020–2022 were selected as samples out of a total of 416 listed on the Indonesia Stock Exchange. Panel data regression analysis is the analysis technique that is applied. This study finds that Corporate Financial Performance is shaped by the interplay of CSR disclosure, tax compliance, and competitive advantage, and that the Corporate Reputation variable is jointly impacted by these independent variables. These findings clarify that businesses who demonstrate environmental concern disclosure combining the The application of CSRD can enhance financial performance, making other elements like competitive advantage and tax compliance more valuable in relation to the overall worth of the business. This study contributes to the corporate reputation literature by validating the mediating role of financial performance on tax and strategic factors